Hubungan Kadar Hemoglobin Dengan Siklus Menstruasi Remaja Putri - Juli Evianna Br Purba; Miftahul Jannah (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2023)
value = 0.000 or valuer rAdolescence is a period of transition between childhood into adulthood, problem that often occurs in adolescence are less nutrition resulted in malnourished. Hb is a quantitative indicator to determine iron deficiency with the most severe level. Menstruation adalahperdarahan derived from this research uterus.Jenis Praeksperimen with the design of "The One Shot Case Study" to obtain information about the menstrual cycle in young girls. The sample in this study were taken by the formula vincean as many as 52 samples. With independent variable hemoglobin levels in young women and adolescents dependent variable menstrual cycle putri.Pada univariate analysis presented in the form of a frequency distribution expressed in absolute frequency which is the number of occurrences and relative frequencies in the form of presentation (%) and on a bivariate analysis used chi-test square.Hasil research shows the majority of respondents have irregular menstrual cycles 61.5% and the mean Hb 10-11gr%, based on chi-square statistical test showedÂ  < = 0.000.r0.005, so it can be concluded that Ho refused and Ha received means there singnifikan relationship between hemoglobin levels with the menstrual cycle in young women are a significant association between hemoglobin levels with the menstrual cycle, where the better levels of hemoglobin, the possibility of a regular menstrual cycle is getting better, with the value.